2012
DOI: 10.28930/jitkt.v4i1.7804
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Species and Structure of Seagrass Fish Community in Tanjung Tiram – Inner Ambon Bay

Abstract: The study was conducted in March -May 2011 Siganus canaliculatus memiliki jumlah komposisi jenis tertinggi sebesar 62,91 %. Nilai struktur komunitas berfluktuasi secara temporal, Indeks dominansi masuk kategori rendah, Indeks keanekaragaman masuk kategori sedang dan Indeks keseragaman masuk kategori labil. Hasil penelitian menunjukkan bahwa secara ekologi ekosistem padang lamun perairan Tanjung Tiram memiliki peranan penting sebagai daerah pemijahan, asuhan, pembesaran dan tempat mencari makan bagi komunitas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
4
0
10
Order By: Relevance
“…Keragaman ikan dalam suatu perairan dapat diketahui dari indeks keragamannya. Semakin kecil nilai indeks keragaman organisme, maka penyebaran individu tiap jenis tidak sama, ada kecenderungan didominasi oleh jenis tertentu (Odum, 1993) dalam Latuconsina et al (2012).…”
Section: Indeks Keragaman (E)unclassified
See 1 more Smart Citation
“…Keragaman ikan dalam suatu perairan dapat diketahui dari indeks keragamannya. Semakin kecil nilai indeks keragaman organisme, maka penyebaran individu tiap jenis tidak sama, ada kecenderungan didominasi oleh jenis tertentu (Odum, 1993) dalam Latuconsina et al (2012).…”
Section: Indeks Keragaman (E)unclassified
“…Dominansi yang cukup besar akan mengarah pada komunitas yang labil maupun tertekan. Indeks dominansi dihitung dengan menggunakan rumus indeks dominanasi dari Simpson (Odum, 1993) dalam Latuconsina et al (2012).  Jika nilai C mendekati 0 (< 0,5), maka tidak ada spesies yang mendominasi.…”
Section: Indeks Dominansi (C)unclassified
“…The highest pH was found in the Halong station, while the lowest pH was found in the Hutumuri station. Some researchers who conducted research in Ambon Island waters reported that the pH range of the waters was between 7.03-7.68 (Rumahlatu and Leiwakabessy 2017), 7.91-8.16 (Gemilang et al 2017), 8.00-8.25 (Latuconsina et al 2012). According to Gemilang et al (2017), terrestrial organic matter carried through rivers as well as the community activities has a significant effect on the pH values of the waters.…”
Section: Conditions Of Environmental Factorsmentioning
confidence: 99%
“…Thus, its existence could protect other smaller seagrass species against stream and waves (Fonseca and Cahalan 1992;John et al 2015). Seagrass beds provide habitat for a fish community (Phinrub et al 2014), the existence of seagrass stand especially E. acoroides (Lotuconsina et al 2012;Ambo-Rappe et al, 2013) and C. rotundata is a vegetative option chosen by the fish species to associate. The association can be seen especially in ST2 where the density of the seagrass was experiencing a decline, especially H. pinifolia, T. hemprichii, and H. minor but the number of fish species available in ST2 was consistent, and so was the fish species in ST1 which was likely stable (Figure 2.E and 2.F).…”
Section: Seagrass Bedsmentioning
confidence: 99%